Energy saving patterns of personnel behaviour in Malaysian office - Ishak, Mohd Hafizal; Ahmad, Md Fauzi; Aziz Satar, Mohamad Azuan; Lee, Ting Kee (ASIAN INSTITUTE OF TECHNOLOGY, 2018)
This research concentrates on determining energy saving patterns that appear in the behavior of staff in Malaysian office buildings, and the variables that affect their behavior. There are two types of variables to be studied, including personalities and environmental factors. Johor Bahru’s office buildings, Malaysia’ workers have been chosen as a source of data for qualitative study. Additionally, descriptive analysis and binary logistic regression have been selected as means for further analyzing inputs, in order to accomplish the research objectives. The result indicates that there are two types of energy saving patterns, specifically Saver and Non-Saver. Based on the results, gender, age, education, income and personal characteristics have all been identified as factors that impact energy saving patterns. In terms of the environmental variable, it has been shown that environmental concern, environmental knowledge, perceived consumer effectiveness, resource saving and income, are all major factors that affect energysaving behaviors. The outcome of this study is crucial for facility management, in obtaining information related to personnel behavior, and adds to the possibility of improving energy saving and conservation in the workplace.